EFFECTS OF LITERATURE CIRCLES AND SCAFFOLDING INSTRUCTIONAL STRATEGIES ON SENIOR SECONDARY SCHOOL STUDENTS' ACHIEVEMENT AND ATTITUDE TO PROSE LITERATURE IN ENGLISH (2012)
Literature indicates that students' poor command of English language, unwillingness to engage in reading tasks and lack of engagement with recommended texts cause poor performance. Previous studies have been carried out on the use of basic literature circles, literature circles with roles and scaffolding strategies to enhance students' reading and writing achievement. However, the use of these strategies in studies conducted in Nigeria especially in the area of prose literature in English is not common. This study therefore investigated effects of these student-centred and socio-cultural strategies on senior secondary school students' achievement and attitude to prose literature in English. It also determined moderating effects of verbal ability and gender on the dependent measures. The study adopted the pretest-posttest, control group quasi-experimental design using a 4x3x2 factorial matrix. Three hundred and eighteen Senior Secondary II students in intact classes from eight senior secondary schools purposively selected from four local government areas of Ogun State were randomly assigned to treatment (basic literature circles, literature circles with roles and scaffolding) and control groups. Three response research instruments: Verbal Ability (r =0.82), Prose Literature in English Attitude Questionnaire (r =0.77), Achievement Test in Prose Literature (r =0.88) and four stimulus instruments: Basic Literature Circles Instructional Guide, Literature Circles with roles instructional Guide, Scaffolding Instructional Guide and Conventional Method Instructional Guide were used for data collection. Seven hypotheses were tested in the study at P<0.05 level of significance. Data collected were analysed using Analysis of Covariance and Multiple Classification Analysis was used to examine the magnitude of the differences among the various groups while scheffe post-hoc was used for pair-wise comparison to explain the significant main effects observed. There was a significant main effect of treatment on students' achievement scores in prose literature (F(3,293) =36.11; P < 0.05). The students exposed to Scaffolding had the highest mean achievement score ( = 16.84) followed by Basic Literature Circles ( = 16.30) then Literature Circles with Roles ( = 15.25) and the Conventional Method ( = 9.93) in that order. However, treatment had no significant main effect on students' attitude to Prose Literature in English (F (3,293) = 33.74; P > 05). In addition, verbal ability and gender had no significant effect on students' achievement and attitude to prose literature in English. There were also no significant interaction effect of treatment and verbal ability; treatment and gender on students' achievement and attitude to the subject. In the same vein, there was no significant three way interaction effect of treatment, verbal ability and gender on students' achievement and attitude to prose literature in English. Student-centred and socio-cultural strategies (literature circles and scaffolding strategies) enhanced students' active engagement with texts and were more effective in promoting students' achievement in prose literature in English. It is, therefore, recommended that teachers of literature especially prose should be encouraged to use these strategies in their lessons.